2004
DOI: 10.1063/1.1814631
|View full text |Cite
|
Sign up to set email alerts
|

The rotational spectrum and dynamical structure of LiOH and LiOD: A combined laboratory and ab initio study

Abstract: Millimeter wave rotational spectroscopy and ab initio calculations are used to explore the potential energy surface of LiOH and LiOD with particular emphasis on the bending states and bending potential. New measurements extend the observed rotational lines to J=7<--6 for LiOH and J=8<--7 for LiOD for all bending vibrational states up to (03(3)0). Rotation-vibration energy levels, geometric expectation values, and dipole moments are calculated using extensive high-level ab initio three-dimensional potential ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…[35] for an extensive literature review). Recently, Higgins et al [35] combined millimeter wave rotational spectroscopy and high level ab initio calculations to explore the potential energy surface of LiOH and LiOD. They found that the molecule is extremely non-rigid and that the structure is linear at equilibrium with r e (OH) ¼ 0.949(2) Å .…”
Section: Diatomic and Triatomic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] for an extensive literature review). Recently, Higgins et al [35] combined millimeter wave rotational spectroscopy and high level ab initio calculations to explore the potential energy surface of LiOH and LiOD. They found that the molecule is extremely non-rigid and that the structure is linear at equilibrium with r e (OH) ¼ 0.949(2) Å .…”
Section: Diatomic and Triatomic Speciesmentioning
confidence: 99%
“…For this reason, it has been the subject of many experimental and theoretical studies (see Ref. [35] for an extensive literature review). Recently, Higgins et al [35] combined millimeter wave rotational spectroscopy and high level ab initio calculations to explore the potential energy surface of LiOH and LiOD.…”
Section: Diatomic and Triatomic Speciesmentioning
confidence: 99%
“…Typically, MSH species exhibit bent geometries in their ground electronic states. In contrast, the MOH counterparts are either linear or quasilinear, 16,17 with the exception of CuOH and ZnOH. 18,19 The geometric preference is attributed to the character of the metal-ligand bond.…”
Section: Introductionmentioning
confidence: 99%
“…These species have all proved to be linear, with the exception of the indium compound, which is bent with an angle of 132°. Some quasilinear behavior is exhibited by MgOH and LiOH [6,21], as well, which both appear to have very low energy bending potentials. However, very few transition metal hydroxides have been investigated by gas-phase spectroscopic methods.…”
Section: Introductionmentioning
confidence: 94%
“…High-resolution spectroscopy of alkali and alkaline-earth hydroxide species has been carried out for several decades, beginning with the work of Lide and collaborators [6][7][8][9][10][11][12][13][14][15][16][17][18]. More recently, investigations of aluminum and indium hydroxides have been performed, providing additional insight [19,20].…”
Section: Introductionmentioning
confidence: 98%